Engine performance and emission of compression ignition engine fuelled with emulsified biodiesel-water. Issue 1 (November 2015) - Maawa, W N; Mamat, R; Najafi, G; Ali, O Majeed; Aziz, A
Abstract: The depletion of fossil fuel and environmental pollution has become world crucial issues in current era. Biodiesel-water emulsion is one of many possible approaches to reduce emissions. In this study, emulsified biodiesel with 4%, 6% and 8% of water contents were prepared to be used as fuel in a direct injection compression ignition engine. The performance indicator such as brake power, brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE) and emissions such as NOx and particulate matter (PM) were investigated. The engine was set at constant speed of 2500 rpm and load from 20% to 60%. All the results were compared to B5 (blend of 95% petroleum diesel and 5% palm oil biodiesel) biodiesel. At low load, the BSFC decrease by 12.75% at 4% water ratio and decreased by 1.5% at 6% water ratio. However, the BSFC increases by 17.19% with increasing water ratio to 8% compared to B5. Furthermore, there was no significant decrease in brake power and BTE at 60% load. For 20% and 40% load there was some variance regarding to brake power and BTE. Significant reduction in NOx and PM emissions by 73.87% and 20.00% respectively were achieved with increasing water ratio to 8%. Overall, it is observed that the emulsified of biodiesel-water is an appropriate alternative fuel method to reduce emissions.